The Role of Blood-Borne Microparticles in Inflammation and Hemostasis - Suades, Rosa; Padró, Teresa; Badimon, Lina (Seminars in Thrombosis and Hemostasis, 2015)
Inflammation has a pivotal role in cardiovascular disease because it contributes to the progression of atherosclerosis, a chronic inflammatory disease of the vessel wall. Microparticles (MPs) have recently emerged as both surrogate markers for different cardiovascular conditions (i.e., biomarkers of vascular inflammation and coagulation) and paracrine biological shuttle modules with influence in target cells. MPs are vesicles that bud off from cells, lack a nucleus, contain a membrane skeleton, and are defined by their size and expression on their surface of antigens specific of parental cells. Interestingly, not only inflammation is one of the main stimuli causing MP release but also MPs, in its turn, can induce, regulate, and even in specific cases reduce inflammation. The present review aims to summarize and update the role of circulating MPs in inflammation and hemostasis with special emphasis on their novel associations and functions. Besides their role as biomarkers of atherosclerotic inflammation, blood-borne MPs possess mechanisms to alter vascular cell milieu, to disseminate proinflammatory mediators, and to spread the inflammatory cascade reaction, causing a chronic inflammation of the vascular wall and aggravating the atherothrombotic process.
Keywords: atherosclerosis; circulating microparticles; hemostasis; inflammation